Pelestarian Sumberdaya Perikanan bagi masyarakat pesisir Untuk Mendukung Ekonomi Biru Dan Kreatif Di Desa Bugbug, Karangasem, Bali - Wardani, Ria Tri; Fadillah, Fadillah; Fitri, Miftahul; Rosada, Rizky Amrina; Maolana, Arman (Universitas Mataram, 2024)
Bali as one of the tourist destinations in Indonesia. Bugbug Village, located in Karangasem Regency, is one of the oldest and largest villages in the sub-district. The people of Bugbug Village come from the lower middle class, with the main livelihood being fishermen. Communities in this coastal area use Pasih Kelod beach as a fishing ground to obtain economic value to meet their needs. However, the public does not yet know what fishing gear can be used and what cannot be used, therefore it is important to carry out outreach regarding the introduction of the fishing gear used and fishing area boundaries. This activity was attended by 12 groups of fishermen as well as the hamlet head of Bug-bug village